The Influence of Cross Equatorial Northerly Surge (CENS) and El Nino Southern Oscillation (ENSO) on ˜ Atmospheric Dynamics in Western Indonesia - Jhon Paul Estomihi Togatorop; Sayful Amri; Jerremy Mezac Sopacua (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2025)
Indonesia's position between the Asian and Australian continents makes its weather highly sensitive to atmospheric interactions from both regions. This study examines the impact of Cross-Equatorial Northerly Surge (CENS) and El Nino˜ Southern Oscillation (ENSO) phasesNeutral, La Nina, ˜ and El Ninoon ˜ atmospheric dynamics over western Indonesia. The analysis focuses on CENS propagation from the southern South China Sea to the west of the Java Sea, comparing atmospheric responses during CENS-ENSO Neutral, CENS-La Nina, ˜ and CENS-El Nino˜ events. Using ERA-5 reanalysis data and CMORPH precipitation data (0.25◦ spatial, hourly temporal resolution), we analyzed sea surface temperature (SST), outgoing longwave radiation (OLR), precipitation, moisture transport, and divergence. Under neutral ENSO conditions, CENS strengthens the Asian monsoon, enhancing moisture transport and convergence over northern Java, leading to increased deep con-vection and precipitation, while Sumatra and Kalimantan experience moisture divergence and reduced cloud cover. During La Nina, ˜ enhanced moisture transport and convergence extend to Kalimantan, further amplifying convective activity and rainfall. In contrast, during El Nino, ˜ the cooling effect of CENS onthe South China Sea weakens, but moisture convergence intensifies over the Java Sea, triggering cloud development despite suppressed convection. These findings highlight the crucial role of CENS-ENSO interactions in modulating regional weather patterns and extreme events, offering insights for improving weather forecasting, disaster mit-igation, and climate modeling in western Indonesia.